Bias‐Polarity Dependent Bidirectional Modulation of Photonic Bandgap in a Nanoengineered 3D Blue Phase Polymer Scaffold for Tunable Laser Application. Issue 16 (17th June 2018) - Wang, Meng; Zou, Cheng; Li, Chenyue; Sun, Jian; Wang, Ling; Hu, Wei; Zhang, Cuihong; Zhang, Lanying; He, Wanli; Yang, Huai
Abstract: Transferring self‐assembly liquid‐crystalline blue phase structure to polymers is emerging as a promising bottom‐up strategy in the nanofabrication of 3D photonic materials and devices. Here a polymer scaffold in blue phase I structure is fabricated with cubic symmetry and its potential application is demonstrated as an electrically tunable mirrorless laser by refilling the scaffold with laser dye‐doped nematic liquid crystal mixture. The templated blue phase exhibits immense thermal stability and sensitive responsive behavior to external electric fields with blueshift of the reflection band under negative bias voltage whereas redshift under positive bias. Moreover, bias‐polarity dependent bidirectional tuning of the laser emission with wavelength range of about 48 nm is achieved in the study. The nanoengineered 3D polymer scaffold with splendid electrical tunability might provide impetus for the preparation of functional hybrid materials and novel device architectures, which have diversified potential applications in reflective full‐color displays, tunable optical devices, and photonic integrated circuits. Abstract : A polymer scaffold in porous 3D nanostructure with cubic symmetry of blue phase I and sensitive electrically stimuli‐responsive characteristic is fabricated. By refilling the scaffold with laser dye‐doped nematic liquid crystal mixture, a templated blue phase laser exhibiting immense thermal stability and bias‐polarity dependent bidirectional tuning of the laser emission is developed.